PENGARUH KESESUAIAN KOMPENSASI, PENERAPAN SISTEM INFORMASI AKUNTANSI, DAN EFEKTIVITAS PENGENDALIAN INTERNAL TERHADAP KECURANGAN AKUNTANSI STUDI PADA BANK PERKREDITAN RAKYAT (BPR) DI KOTA BANDA ACEH - Ryan Muhammad; Ridwan Ibrahim (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The purpose of this study was to study the effect of compensation suitability, the application of accounting information system, and the effectiveness of internal control to the accounting fraud studies at rural banks in banda aceh city. Independent variables consist of compensation suitability (X1), application of accounting information system (X2) and effectiveness of internal control (X3) and dependent variable that is fraud accounting (Y). The population of the study were all those who received the delegation of authority and responsibility to engage in the use of budgeted funds, accounting executives, and possible employees to commit frauds occurring to the Banda Aceh City Rural Bank. The respondents of this research are branch head, finance, accounting and internal audit at Banda Aceh BPR, amounting to 32 (thirty two), the reason for the election is due to the Head of branch, finance, accounting and internal audit Working in the field has links to record keeping, financial reporting as well as evaluations and supervision so there is considerable opportunity to commit fraud. This research uses census method. The test results show that (1) compensation appropriateness, application of accounting information system and effectiveness of internal control together affect fraud at BPR Kota Banda Aceh, (2) Compensation suit affects fraud in Banda Aceh City Rural Bank, (3) Implementation Accounting information system influences fraud on BPR Kota Banda Aceh, (4) Internal Control affects fraud at BPR Kota Banda Aceh